Social Competency of Indonesian Language Lecturers Buana Perjuangan University, Karawang - Repelita, Tridsays; Hidayat, Sholeh; Anriani, Nurul; Nugraha, Yogi; Prihamdani, Depi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Lecturers have a strategic role in the formation of qualified and highly competitive graduates, not only as teachers, but also as academic supervisors, researchers, and role models. One of the crucial aspects of competence is social competence, namely the ability to communicate and interact effectively with students, peers, education staff, parents, and the community. This study aims to examine the social competence of Indonesian lecturers at Buana Perjuangan University Karawang in the context of learning and academic life. This study uses a qualitative approach with data collection techniques through in-depth interviews and documentation. The results of the study show that Indonesian lecturers at UBP Karawang have good to very good social competence, which is reflected in polite and inclusive communication, cross-unit collaboration, and concern for the diversity of student backgrounds. Lecturers also show openness to feedback, the ability to create a conducive learning atmosphere, and active contributions in the tridharma activities of higher education. These findings confirm that social competence not only supports learning success, but also strengthens an inclusive, ethical, and collaborative academic culture.